Kyrgyzstan Universities’ Profile in Terms of Preparing Students for the Future: Student Opinions - Gul, Yavuz Ercan (Asian Journal of Education and Training, 2019)
Higher education in Kyrgyzstan has undergone a great deal of change in terms of quantity and quality since Kyrgyzstan’s independence. Today, while there are many higher education institutions in the country, there are discussions about the quality of these institutions. The main purpose of this research is to determine the role of Kyrgyz universities in preparing students for the future. The research is designed as a mixed research design applying qualitative and quantitative data collection techniques together. For the qualitative data of the study, the research group consisted of 10 students and the quantitative data were collected from 312 students studying in three different universities. As a result of the research, it is understood that university students regard their universities as inadequate in terms of library, technological equipment, foreign language teaching, current craft knowledge, and social fields. The findings were discussed with other studies in the literature and some suggestions were made for the improvement of Kyrgyzstan universities.